1998
DOI: 10.1021/om970459a
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Decomposition of a Pentacoordinate Spirobis[1,2-oxasiletanide]

Abstract: Sequential treatment of diphenylbis((phenylthio)methyl)silane with lithium naphthalenide, hexafluoroacetone, and then aqueous NH4Cl gave the (β-hydroxyalkyl)diphenyl((phenylthio)methyl)silane 8, Ph2Si(CH2SPh)CH2C(CF3)2OH, a hydroxyl group of which was protected with methoxymethyl to afford the corresponding methoxymethyl ether 9a. Similarly, the reaction of 9a with hexafluoroacetone followed by deprotection of the methoxymethyl group yielded the diphenylbis(β-hydroxyalkyl)silane 11, Ph2Si[CH2C(CF3)2OH]2. Seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Then, a [2+2] retro-cycloaddition, probably induced by a release of ring strain in the pentacoordinate intermediate 5, similarly to the Perterson olefination reaction, affords 4. [20,21] The efficient stabilization of silanoic acid 6 by coordination of the donor/acceptor iminophosphorane ligand 7 on the silanone function was supported by DFT calculations revealing the strong exergonic nature of the reaction (DG = À44.2 kcal mol À1 , Scheme 5). Interestingly, in spite of this stabilization, the coordination of ligand 7 does not affect the acidity in the gas phase.…”
Section: Methodsmentioning
confidence: 88%
“…Then, a [2+2] retro-cycloaddition, probably induced by a release of ring strain in the pentacoordinate intermediate 5, similarly to the Perterson olefination reaction, affords 4. [20,21] The efficient stabilization of silanoic acid 6 by coordination of the donor/acceptor iminophosphorane ligand 7 on the silanone function was supported by DFT calculations revealing the strong exergonic nature of the reaction (DG = À44.2 kcal mol À1 , Scheme 5). Interestingly, in spite of this stabilization, the coordination of ligand 7 does not affect the acidity in the gas phase.…”
Section: Methodsmentioning
confidence: 88%
“…4 Most of them were isolated as stable compounds by introduction of the Martin ligand. 5 Furthermore, we have also synthesized spiro compounds bearing two oxetane rings, namely, spirobi[1,2-oxaphosphetane], 6 , spirobi[1,2-oxasiletanide], 7 and spirobi[1,2-oxaselenetane]. 8 In the last account, 9 we reported four-membered heterocycles containing highly coordinated group 16 elements.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For the purpose of elucidating the influence of ring size of the spiro-ring system on the reactivity of the heteracyclobutanes, we have investigated the synthesis and reactivity of compounds 1 and 2, which have two oxaphosphetane and oxasiletane rings, respectively, and found that 1 undergoes double olefin extrusion, 4 while 2 undergoes homo-Brook rearrangement to give the corresponding alcohol. 5 On the other hand, we have recently found that the oxirane formation reactions from pentacoordinate 1,2l 6 -oxathietanes 3a,b or tetracoordinate 1,2l 4 -oxaselenetanes 4a,b proceed with retention of configuration, 6 which is the first example for the oxirane formation without backside attack of oxide anion on the carbon attached to the chalcogen atom, in sharp contrast to the Corey-Chaykovsky reaction. 7 These results prompted us to study tetracoordinate 1,5-dioxa-4l 4 -selenaspiro [3.3]heptanes, a novel type of a spiroselenurane bearing two oxaselenetane rings.…”
mentioning
confidence: 97%
“…Fig.1ORTEP drawing of trans-trans-9 with thermal ellipsoid plot (30% probability for all non-hydrogen atoms). Selected bond lengths (Å), bond angles (°) and torsion angles (°): Se1-O1 1.971(4), Se1-O2 1.955(4), Se1-C1 1.979(6), Se1-C3 1.978(6), C1-C2 1.532(8), C2-O1 1.388(6), C3-C4 1.531(8), O2-C4 1.392(7); O1-Se1-O2 155.26(18), C1-Se1-O1 71.1(2), Se1-C1-C2 90.0(4), C1-C2-O1 103.7(5), Se1-O1-C2 94.7(3), C1-Se1-C3 109.2(3), O2-Se1-C3 71.9(2), O2-C4-C3 104.3(5), Se1-C3-C4 89.1(4); Se1-C1-C2-O1 25.9(5), Se1-C3-C4-O2 26.1(5).…”
mentioning
confidence: 99%